2005
DOI: 10.1590/s0104-83332005000100006
|View full text |Cite
|
Sign up to set email alerts
|

A feminização persistente na qualificação profissional da enfermagem brasileira

Abstract: Este artigo tece reflexões sobre o universo sociohistórico do cuidado de saúde na perspectiva da divisão sexual do trabalho. A enfermagem é o campo profissional analisado e espelha a feminização no setor. Nesse sentido, pode-se afirmar que persiste a feminização na enfermagem brasileira, o que pode ser observada tanto na qualificação universitária como nos níveis médio e técnico. A enfermagem no setor da saúde representa o maior contingente de trabalhadoras e trabalhadores, sendo marcada pela seletividade com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
83

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 0 publications
2
18
0
83
Order By: Relevance
“…The fact that the majority of the students were women confirms that the profession still remains female, as shown in the study (11) conducted in 2005, which indicates the feminization both in the university qualification, as well as at the technical level. It was observed that the majority of the students were young adults, corroborating the study (12) , which shows that the Nursing undergraduate degree course is composed, mostly by young adults.…”
Section: Discussionmentioning
confidence: 68%
“…The fact that the majority of the students were women confirms that the profession still remains female, as shown in the study (11) conducted in 2005, which indicates the feminization both in the university qualification, as well as at the technical level. It was observed that the majority of the students were young adults, corroborating the study (12) , which shows that the Nursing undergraduate degree course is composed, mostly by young adults.…”
Section: Discussionmentioning
confidence: 68%
“…Visibility of the physicians' work and invisibility of the nurses' work is compared in a study (15) that indicates that the first is made up of concrete and quantifiable actions, with a higher wage and payment for each action made, whereas the second follows the orders of the first even with their concrete, continuous and essential existence.…”
Section: Resultsmentioning
confidence: 99%
“…Nursing became a field of knowledge and practice with female dominance associated with the role of wife-mother, who has always been a healer and holder of informal knowledge of health practices (7) . However, the inclusion of male professionals in the field has been observed.…”
Section: Discussionmentioning
confidence: 99%